135 One night of mild sleep restriction affects EEG and behavioural measures of vigilance. (3rd May 2021) - Gibbings, Aaron; Ray, Laura; Berberian, Nareg; Zandi, Ali Shahidi; Owen, Adrian; Comeau, Felix; Fogel, Stuart
Abstract: Introduction: Much is known about the behavioural and cognitive consequences of chronic sleep loss but relatively little is known about the changes in brain activity associated with reduced vigilance after mild and acute sleep loss. Mild and acute sleep loss is generally thought to be innocuous despite research showing emotional processing, visual attention and behavioural responding are all negatively impacted by even small amounts of sleep loss. The current study investigated behavioural, cognitive, and electrophysiological consequences of mild (i.e., a couple of hours) and acute (i.e., a single night) sleep loss via simultaneous behavioural and physiological measures of vigilance. Methods: Participants (N = 23; 18 females, Mage = 22 ± 3 years) came into the lab (from ~12 pm to 3 pm) for two testing days after sleeping from 1 am to 6 am (Sleep Restriction), or from 12 am to 9 am (Normally Rested). Brain activity was recorded using electroencephalography (EEG) from 15 scalp derivations, while vigilance was assessed simultaneously using the psychomotor vigilance task (PVT). Results: Vigilance was reduced in the Sleep Restricted vs. Normally Rested condition, (F(1, 22)=9.02, p=0.007). This was exacerbated over the course of performing the PVT, (F(5, 110)=8.12, p<0.001). Sleep Restriction also resulted in increased intensity of alpha burst activity compared to the Normally Rested condition (F(1, 20)=6.19, p=0.022). Lastly, EEG spectral power differed between restriction sleep conditions across deepening stages of sleep onset, particularly for frequencies that reflect arousal e.g., delta, alpha and beta activity (F(1, 20)>5.52, p<0.029). Conclusion: These results suggest that even a small amount of sleep loss, occurring on only one night significantly reduces vigilance and impacts the physiology of the brain in ways that reflect reduced arousal. Understanding the neural correlates and cognitive processes associated with sleep loss may lead to important advancements in identifying and preventing potentially deleterious or dangerous, sleep-related lapses in vigilance (e.g., in the classroom, workplace), and when lapses in vigilance can be life-threatening (e.g., while driving). Support (if any):